Economic and social factors of the state participation impact on the development of pilgrimage tourism - Uzakov Norboy Professor; Uzakov Dzhamshid Norboevich (THE INNOVATION ECONOMY, 2026)
The article analyzes the economic and social factors of state participation in the development of pilgrimage tourism. Pilgrimage tourism is considered not only as a means of increasing the country’s competitiveness in the international tourism market, but also as an important factor in regional economic development, job creation, and improving the living standards of the population. Regulatory and legal acts, investment programs, and infrastructure projects implemented by the state are identified as key factors in ensuring the sustainable development of pilgrimage tourism. At the same time, the effective system of state regulation contributes to strengthening socio cultural integration, preserving and promoting spiritual and religious heritage. The study pays special attention to the role of state policy, public-private partnership, and community participation in ensuring the economic efficiency and social significance of pilgrimage tourism.